20. Status of coral reefs and associated ecosystems in southern tropical America: Brazil, Colombia, Costa Rica, Panamá and Venezuela (2008)
The coastal environments in Southern Tropical America are characterized by strong land influences with numerous large rivers, including the Amazon, Orinoco and Magdalena, introducing large amounts of sediments that inhibit the development of extensive coral reefs. Rainfall is among the highest in the world, therefore water turbidity and sedimentation are high. Furthermore, there are several major upwellings (Perú, Gulf of Panamá, Gulf of Papagayo, eastern Colombian Caribbean, and eastern Venezuela) that also reduce reef growth. The best coral reefs are on the Caribbean coasts of Panamá and associated with islands off Colombia and Venezuela. Coral formations are comparatively smaller on the Pacific side, and occur principally along the Costa Rica-Panamá coast.